A bibliometric analysis of literature on the out-of-pocket expense in health in Latin America - Mougenot, Benoit (2022)
Objetive: perform a bibliometric analysis of the scientific production on out-of-pocket expense (OOPE) published in Latin America from the period 2002 to 2020 is conducted. The study: we use the Scopus database to select related articles about OOPE in Latin America. Bibliometric indicators were analyzed using Bibliometrix and Biblioshiny R packages. Findings: we identified 207 documents and 828 authors during the period 2002-2020. The number of publications increased (12.62% annual growth rate). “Salud Publica de Mexico” was the leading journals in number of publications. The majority of publications came from developing country collaboration with developed countries such as United States or United Kingdom. Mexico was the most productive and cited country in OOPE in Latin America. Conclusions: the documents published in journals related to OOPE in Latin America are increasing, being Mexico the most productive and cited country in out-of-pocket expense fields in the region.